Profile of students' concept understanding in kinematics - Handhika, Jeffry; Widiyaningrum, Saristi; Denata, Sukma Ayu Aprillia (Journal of Physics: Theories and Applications, 2023)
This research aims to profile the understanding of physics concepts in kinematics material. Teachers need information on understanding physics concepts in designing their learning. The profile of understanding the concept of kinematics is revealed by administering a concept understanding test. The total number of tests for understanding the concept of kinematics is 30 items. The concept understanding profile is categorized into five indicators: (1) interpretation, (2) classifying, (3) inference, (4) comparing, and (5) explaining—the test applies to 49 students at SMA and MA in Madiun. Based on the profile description analysis results, it was obtained that students had a good percentage of the concept understanding indicator component (39.54%) and the smallest percentage of the interpretation indicator (17.60%). These results can be used as recommendations for facilitators and researchers in determining the learning model that will be applied and the concept of understanding the research topic that will be carried out.